2022
DOI: 10.3390/biomedicines10051213
|View full text |Cite
|
Sign up to set email alerts
|

Administration Routes as Modulators of the Intrahepatic Distribution and Anti-Anemic Activity of Salicylic Acid/Fe3O4 Nanoparticles

Abstract: The liver is a key organ in the pharmacokinetics of iron oxide nanoparticles (IONPs). This paper examined how the intravenous (IV) or intragastric (IG) route of administration influenced the intrahepatic distribution or therapeutic effects of IONPs. Wistar rats, some with bleeding-induced anemia, and iron oxide nanoparticles functionalized with salicylic acid (SaIONPs), with an average hydrodynamic diameter of 73 nm, compatible with rat sinusoid fenestrations, were used in this study. Light microscopy and mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 59 publications
1
2
0
Order By: Relevance
“…With an average particle size of 8.52 ± 1.41 nm (determined by TEM analysis), the synthesized Fe 3 O 4 -SA NPs fit within the desirable dimensional range, suggesting the applicability of the obtained materials for bionanomedicine purposes. Moreover, studies have indicated the potential of Fe 3 O 4 -SA NPs of comparable hydrodynamic diameters with those obtained by our DLS analysis (V1-V5) for several biomedical uses, including the management of bleeding-induced anemia [63], melanoma [64,65], and vascular nanoblockages [66].…”
Section: Discussionsupporting
confidence: 67%
“…With an average particle size of 8.52 ± 1.41 nm (determined by TEM analysis), the synthesized Fe 3 O 4 -SA NPs fit within the desirable dimensional range, suggesting the applicability of the obtained materials for bionanomedicine purposes. Moreover, studies have indicated the potential of Fe 3 O 4 -SA NPs of comparable hydrodynamic diameters with those obtained by our DLS analysis (V1-V5) for several biomedical uses, including the management of bleeding-induced anemia [63], melanoma [64,65], and vascular nanoblockages [66].…”
Section: Discussionsupporting
confidence: 67%
“…Previous studies have shown that SaIONPs have effectively overcome these challenges and demonstrated versatility for oral administration. Their presence has been identified in the lamina propria and capillaries of the stomach, small intestine, and proximal colon, indicating their resilience to pH variations and successful absorption throughout the gastrointestinal tract [19]. The toxicity over the liver is expected to occur at much higher concentrations of cumulative doses of SaIONPs corresponding to 6 mg/kg Fe 3 O 4 .…”
Section: Discussionmentioning
confidence: 99%
“…Although intraperitoneal and intravenous pathways are the most studied administration routes for SaIONPs, oral administration is better tolerated by the patient and has greater convenience. [19].…”
Section: Introductionmentioning
confidence: 99%